The Influence of Brand Image, Brand Love, and Perceived Value on Luxcrime Comics Customer Loyalty in East Surabaya - Nurul Hidayati; Lia Nirawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
The growth of the cosmetics industry is increasing, creating competition among companies to attract customers. The purpose of this research is to identify the effect of brand image, brand love and perceived value on customer loyalty in Luxcrime Cosmetics in East Surabaya. This research is included in the associative type with a quantitative approach, the data was analysed using the Statistical Packagel for the Social Sciences 27 for Windows software with (validity test, reliability test, hypothesis testing, classical assumption test). This data collection technique uses questionnaires with sampling techniques from the population of users of luxury cosmetic products in East Surabaya with probability sampling techniques. Thus, 150 respondents were obtained based on the Yamane and Isaac and Michael formulas with the criteria of living in East Surabaya and having bought/used Luxcrime at least 2 times. The study results show that 1) the brand image variable has a partial effect on customer loyalty, 2) the brand love variable has no partial effect on customer loyalty, and 3) the perceived value variable has a partial effect on loyalty. The other results show that the independent variables, namely brand image, brand love and perceived value, have a positive and significant effect on customer loyalty at the same time.